Comparative study of the nutritional, phytochemical and mineral compositions of the nuts of tropical almond (Terminalia catappa) and sweet almond (Prunus amygdalus) - R.A. Salawu; A.F. Onyegbula; I.O. Lawal; S.A. Akande; A.K. Oladipo (Ruhuna Journal of Science, 2018)
The study was conducted to compare the nutritional, phytochemical and mineral compositions of Tropical almond with Sweet almond. Sample of Terminalia catappa nuts were collected within the premises of Nigerian Stored Products Research Institute (NSPRI), Ilorin, Nigeria while Prunus amygdalus was purchased from Shoprite Palms Mall Ilorin, Nigeria. Proximate, phytochemical and mineral analyses were carried out using standard procedures. Results showed that T. catappa was significantly (p<0.05) high in ash (4.84%), crude fibre (15.54%), carbohydrates (2.91%) and some mineral elements such as potassium, zinc, iron, magnesium and copper. Prunus Amygdalus was significantly (p<0.05) high in ether extract (50.96%) while no significant difference (p>0.05) was recorded in their protein contents (33.00 and 32.89% respectively). P. amygdalus was significantly (p<0.05) high in phytochemicals such as tannin (748.49µg/g), phenols (1,781.50 µg/g), flavonoids (456.38 µg/g), saponin (158.70 µg/g) and alkaloids (240.11µg/g) while T. catappa was significantly (p<0.05) high in glycosides (220.27µg/g).The differences in phytochemicals might be due to the differences in drying and other processing methods. T. catappa can well compete with P. amygdalus if the value chain is improved upon by proper packaging and storage for commercial purposes.